1996
DOI: 10.1093/tropej/42.6.362
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1-beta, tumour necrosis factor-alpha, islet-cell antibody, and insulin secretion in children with thalassemia major on long term blood transfusion

Abstract: In vitro, cytokines like interleukin-1-beta (IL-1-B) and tumour necrosis factor-alpha (TNF-A) inhibit insulin release and can destroy islet B-cells. We measured blood levels of IL-1-B, TNF-A, and islet cell antibody (ICA) in 20 children with IDDM, 20 of their non-diabetic siblings, 20 children with thalassemia major on long-term hypertransfusion therapy and iron chelation, and 10 normal age-matched children. In the non-diabetic and thalassemic children we investigated the early phase of insulin release after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Recently, several studies reported a long period of insulin resistance preceding overt diabetes mellitus in thalassaemic patients [4,7,9,10,13,21,23,27]. Because of the inverse relation between insulin sensitivity and insulin secretion, insulin resistance in patients at risk for type 2 diabetes mellitus is associated with hyperinsulinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies reported a long period of insulin resistance preceding overt diabetes mellitus in thalassaemic patients [4,7,9,10,13,21,23,27]. Because of the inverse relation between insulin sensitivity and insulin secretion, insulin resistance in patients at risk for type 2 diabetes mellitus is associated with hyperinsulinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of diabetes among thalassemia patients has been reported to range from 2.3 to 24% (7–10). Although insulin deficiency, secondary to pancreatic islet iron deposition, has been considered the principle cause of the abnormalities in glucose metabolism observed in thalassemics (11–13), other studies have reported hyperinsulinemia with oral glucose tolerance testing, suggesting a role for insulin resistance in mediating these metabolic abnormalities (14, 15). Hemosiderosis, liver infections, and genetic factors seemed to be crucial in the development of diabetes (16, 17).…”
mentioning
confidence: 99%
“…There is strong evidence of an association between endothelial cell activation and vascular complications in patients with β-thalassemia [6], whereas activation of the vascular endothelium is considered an important facet of inflammation, atherosclerosis [27,28,29], vasculitis and thrombosis [30,31,32,33,34,35,36]. However, the underlying mechanism of an association between immunomodulation and cardiovascular complications in these patients is not fully known.…”
Section: Introductionmentioning
confidence: 99%